89 First-in-human CAR T targets cleaved MUC1, the growth factor receptor form. (10th December 2020) - Smagghe, Benoit; Stewart, Andrew; Huang, Pengyu; Swanson, Tyler; Page, Danica; Carter, Mark; Grant, Trevor; Specht, Jennifer; Bamdad, Cynthia
Abstract : Background: Minerva Biotechnologies has opened a Phase I 1st-in-human CAR T clinical trial, NCT-04020575, for metastatic breast cancers at the Fred Hutchinson Cancer Research Center. huMNC2-CAR44 targets the truncated extra cellular domain of MUC1* (muk 1 star), which is the transmembrane cleavage product that remains after MUC1 is cleaved and the tandem repeat domain is shed from the cancer cells. No therapeutic that targets MUC1* has ever been tested in humans. All previous, failed attempts to therapeutically target MUC1 have targeted the tandem repeat domains, which are cleaved and shed from the surface of cancer cells. MUC1 cleavage increases as tumor stage increases. Cleavage and shedding of the tandem repeat domain unmasks an ectopic binding site for onco-embryonic growth factor NME7AB. The antibody fragment that targets the CAR to the tumor competes with NME7AB for binding to this same ectopic site. MUC1* growth factor receptor is activated when onco-embryonic growth factor NME7AB dimerizes its truncated extra cellular domain. Methods: Autologous huMNC2-CAR44 T cells undergo a short 11-day manufacturing process, which includes an antigen stimulation step and preserves many of the cells in the naïve and central memory state. Patients are pre-treated with standard Cy-Flu lymphodepletion. Dose escalation phase is standard 3 × 3 with a starting dose 3.3 × 10e5 CAR T cells and going up to 1.0 × 10e7 cells. Patients are eligible if biopsy is greater than or equal to 30% reactive with MNC2 in a CLIA validated diagnostic assay. Results: In vitro, huMNC2-CAR44 T cells killed cancer cells, but not non-cancer cells even if they expressed MUC1 or a normal form of cleaved MUC1. In NSG mice (n>300), huMNC2-CAR44 T cells eliminated MUC1* positive tumors from implanted breast cancer cells. A single CAR T cell injection eliminated tumors for 100 days; control animals had to be sacrificed at Day 20. Further, huMNC2-CAR44 T cell mediated killing increased as MUC1* density increased. In tissue micro array studies, huMNC2-scFv recognized 95% of breast cancers, across all subtypes, 83% ovarian, 78% pancreatic and 71% of lung cancers. huMNC2-scFv showed almost no binding to normal tissues and no staining of critical organs. Although patient recruitment has been slowed by COVID-19, preliminary results indicate CAR T cell expansion and possible efficacy. Conclusions: Preliminary results show that patients experienced robust CAR T cell expansion with CAR-positive T cells persisting at Day 60 post huMNC2-CAR44 T cell treatment. Possible signs of efficacy were measured. Trial Registration: NCT04020575